PENGEMBANGAN MATERI QIRO’AH BERBASIS FUN LEARNING MENGGUNAKAN MEDIA QUIZIZZ DI MIN 1 PALI - Erista Dinanti, Nabilla; Imron, Kristina; Nazarmanto, Nazarmanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop and examine the effectiveness of Quizizz-based fun learning media in improving students’ qirā’ah (Arabic reading) skills at grade VI of MIN 1 PALI. The research employed the Research and Development (R&D) method, producing a Quizizz-based instructional media product. The research subjects consisted of 24 students divided into an experimental class and a control class, with 12 students in each group. Data were collected through observation, interviews, documentation, questionnaires, and tests in the form of pre-tests and post-tests. Data analysis techniques included normality tests, homogeneity tests, validity tests, independent t-tests, and N-gain analysis. The results revealed a significant difference between the learning outcomes of the experimental and control classes. The average post-test score of the experimental class was higher than that of the control class, indicating that Quizizz-based fun learning media is effective in improving students’ qirā’ah skills. In addition, the implementation of this media increased students’ motivation, enthusiasm, and active participation during the learning process. Therefore, Quizizz-based fun learning media is considered effective and feasible as an alternative instructional medium for Arabic reading instruction at the elementary school level.